How do you solve using gaussian elimination or gauss-jordan elimination, 2x - 3y = 52x3y=5, 3x + 4y = -13x+4y=1?

1 Answer
Nov 27, 2016

x=1, y=-1 x=1,y=1

Explanation:

We can write the system of linear equation in matrix vector form

A ulx = ulb

( (2,-3), (3,4) ) ( (x), (y) ) = ( (5), (-1) )

So the Augmented Matrix is:

( (2,-3,|,5), (3,4,|,-1) )

We can now perform elementary row operations:

( (2,-3,|,5), (3,4,|,-1) ) stackrel(1/2R_1 rarr R_1)(rarr) ( (1,-3/2,|,5/2), (3,4,|,-1) )

( (1,-3/2,|,5/2), (3,4,|,-1) ) stackrel(R_2-3R_1 rarr R_2)(rarr) ( (1,-3/2,|,5/2), (0,17/2,|,-17/2) )

And so:
17/2y=-17/2 => y=-1

Back substituting into R1:
x - 3y/2 = 5/2 => x+3/2=5/2 => x=1